The diminutive in the Linguistic Landscape of Madrid - Hu, Jingyuan; Sáez Rivera, Daniel (Círculo de Lingüística Aplicada a la Comunicación, 2021)
Since the seminal article by Landry and Bourhis (1997), and especially after the monographic issue edited by Gorter (2006), the research on the Linguistic Landscape (LL) or the written signs placed in the urban landscape has aroused increasing attention in the field of Sociolinguistics and connected disciplines. The studies on the LL in Spain have focused above all on the coexistence of Spanish and foreign languages, but lesser in number have been those works dedicated to the analysis of language features in monolingual signs in Spanish, and in this case the presence of Hispanoamerican varieties and the processes of word-formation used have been the main point of interest (Pons 2011, Sáez 2015), as well other dialect idiosyncrasies coming from America (Castillo / Sáez, 2012). A case particularly striking is the use of diminutives in the LL, our research objective here. Therefore, we offer here an analysis of a corpus of 40 photos with diminutives which have been serendipitously captured using digital cameras and cell phones in the streets and supermarkets of Madrid between 2017 and 2020. According to the data obtained, we will classify the tokens of diminutives in the types of interactive use, lexicalization and branding, and we will also ponder on the discourse functions of the several uses of diminutives.